Spectrum sharing schemes in cognitive radio networks based on collusion formation - Xue-song TAN; Chao LIN; Wei GUO (Tongxin xuebao)
When multiple primary network (PN) with different interests competes to offer spectrum access opportunities for a single secondary network,a spectrum sharing scheme based on a repeated game model could be adopted to form a colluded monopoly for the licensed spectrum so as to maximize their total transmission utility.However,when a does not value its future transmission utility enough,it might choose to deviate from the present colluded monopoly to obtain a transmission utility larger than its monopoly utility,which then reduces the current and future transmission utilities of all other PN.Two new strategies were thereby proposed to produce a more flexible and credible spectrum sharing monopoly among all PN.Numerical simulation shows that,compared with the existing triggering strategy,the proposed strategies can effectively increase the overall transmission utility of all PN.